Peran Islam dalam Kepemimpinan Kenegaraan Indonesia - Fazrin, Dinda Nurainun; Nurlaela, Ica; Illahi, Rumaisyah Septian Nuur; Fajrussalam, Hisny; Nabilah, Sarah (Lembaga Yasin AlSys, 2023)
The Indonesian state has many basic differences that are unique, such as differences in tradition, culture, religion, race, and many other things. Most of the Indonesian people embrace Islam and in civilization in Indonesia, Indonesia needs pioneers who are able to bring about extraordinary changes and progress for individuals and the country. This research points to the determination of the share of Islam in the Indonesian state power. The strategy used in the preparation of this article is the literature study method, both literary sources, such as books, journals, articles, and others. The results of this study indicate that the pattern of Indonesian leadership really needs the role of Islam and also requires a leader like Rasulullah. By being able to emulate the leadership characteristics of the Prophet, the leaders of the Indonesian nation will understand how to do it in accordance with the goal of forming Indonesia into an advanced and prosperous nation. Besides that, their leaders will understand how to make their country much better and know how a prophet Muhammad was clever in leading the nation to become a prosperous nation.